2020
DOI: 10.1002/anie.201915944
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable Metal‐, Azide‐, and Halogen‐Free Method for the Preparation of Triazoles

Abstract: A scalable metal‐, azide‐, and halogen‐free method for the synthesis of substituted 1,2,3‐triazoles has been developed. The reaction proceeds through a 3‐component coupling of α‐ketoacetals, tosyl hydrazide, and a primary amine. The reaction shows outstanding functional‐group tolerance with respect to both the α‐ketoacetal and amine coupling partners, providing access to 4‐, 1,4‐, 1,5‐, and 1,4,5‐substituted triazoles in excellent yield. This robust method results in densely functionalised 1,2,3‐triazoles that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 43 publications
0
14
2
Order By: Relevance
“…Condensation of p-toluene sulfonylhydrazide 9 with an aqueous solution of dimethoxyacetaldehyde 8 proceeded smoothly in methanol to give the intermediate hydrazone 10 after 2 h. [20] Addition of benzylamine (11) directly to the reaction mixture and heating the resulting solution in a sealed tube at 75 C for 16 h gave 65% N-benzyltriazole 12 (Entry 1, Table 1). Surprisingly, in contrast to literature observations [18], addition of triethylamine (1.1 equiv) lowered the yield of 12 to 57% (Entry 2). Examination of the literature surrounding the Sakai reaction suggests that chlorovinyldiazene 13 is a potential intermediate in the trans-formation [21].…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Condensation of p-toluene sulfonylhydrazide 9 with an aqueous solution of dimethoxyacetaldehyde 8 proceeded smoothly in methanol to give the intermediate hydrazone 10 after 2 h. [20] Addition of benzylamine (11) directly to the reaction mixture and heating the resulting solution in a sealed tube at 75 C for 16 h gave 65% N-benzyltriazole 12 (Entry 1, Table 1). Surprisingly, in contrast to literature observations [18], addition of triethylamine (1.1 equiv) lowered the yield of 12 to 57% (Entry 2). Examination of the literature surrounding the Sakai reaction suggests that chlorovinyldiazene 13 is a potential intermediate in the trans-formation [21].…”
contrasting
confidence: 99%
“…Recently, both ourselves and a group from Pfizer simultaneously reported that a-ketoacetals could be used as effective triazole precursors through a one-pot, three-component synthesis leading to a simple method for the preparation of 4-, 1,4-, 1,5and 1,4,5-substituted triazole products. [18,19] We believed that this method would be applicable to a novel procedure to access 1-substituted 1,2,3-triazoles. Within this work we describe our findings which show the use of readily available 2,2-dimethoxyacetaldehyde 8 as a precursor to this important heterocycle through the reaction with p-toluene sulfonylhydrazide ( 9) and a primary amine (7, Fig.…”
mentioning
confidence: 99%
“…and are considered as key building blocks in pharmaceutical industry [6][7][8][9]. Thus, they marked their presence as prominent scaffolds in many drug molecules such as tazobactam, cefatrizine, rufinamide and JNJ-54175446 (Scheme 1a) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, enaminones [40] and α ‐chlorotosylhydrazone [41] could be utilized in azide‐free tosylhydrazone‐mediated cyclization reactions with primary arylamines. More recently, a proof of concept on the synthesis of the 1,5‐regioisomers from α ‐ketal aldehydes, primary amines and tosyl hydrazine was established by Clark et al [42] . However, a common drawback of the methods present in the literature is the fact that the starting materials are often not commercially available or require a multistep synthesis.…”
Section: Introductionmentioning
confidence: 99%